The influence of high technologies on the formation of high-order consciousness = Wpływ technologii zaawansowanej na kształtowanie myślenia wyższego rzędu - Abramova, Mariya Alekseevna; Krasheninnikov, Valeriy Vasilievich; Kamenev, Roman Vladimirovich (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Keywords: high-order thinking, development of thinking, education system, digital technologies. The authors address the problem of the development of high-order thinking. The article offers an overview of approaches to actualizing the transformation of the concept of reflexive design thinking to higher-order thinking. The authors concluded that society?s demand for higher-order thinkers can be solved by reviewing the construction of the learning process. This hypothesis was tested on the example of the B.A. students of vocational training at Novosibirsk State Pedagogical University (NSPU). The results of the experiment led to the conclusion about the possibility of using high technology as a factor contributing to the development of high-order thinking (including self-consciousness).
Keywords: high-order thinking; development of thinking; education system; digital technologies; myślenie wyższego rzędu; rozwój myślenia; system edukacji; technologie cyfrowe